Correlational Study between Students’ Habit in Watching English Movie and Their Vocabulary Acquisition in English Education Study Program at Pattimura University - Relmasira, Mega Victoria; Lewier, Christian Albert; Lekatompessy, Jeny (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2023)
The aim of this study was to know the correlation between students’ habit in watching English movie (X) and their vocabulary acquisition (Y) on the 5th semester students of English Education Study Program of Pattimura University. A correlational study under quantitative research was applied to conduct this study. There were 40 students taken as the sample of this research. In collecting the data, the researcher used questionnaire and vocabulary test. For the data analysis, the researcher used Pearson Product Moment Correlation. Subsequently, the research finding indicated that there is a correlation between X and Y variables. The data analysis showed that the obtained correlation coefficient value (r) is 0.614 with the significant value 0.00. This indicated that the higher students’ habit in watching English movie, the higher their vocabulary acquisition will be. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. In conclusion, there is a significant and positive correlation between students’ habit in watching English movie and their vocabulary acquisition.